Financing sustainable development in Africa: Taking stock, and looking forward - Opeyemi Oluwabunmi Adejumo; Uchenna Rapuluchukwu Efobi; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
Financing sustainable development in Africa requires financing options that is best for development in the region without further escalating other societal problems. This chapter takes stock of financing options previously advocated for financing development in the African region such as development assistance and foreign investment. By considering its implication on development outcomes like poverty, inequality, and aggregate human development, some drawbacks still exist. Therefore, the chapter identifies, reconfigures and reinvents other financial flows such as mutual support networks, agricultural cooperatives, crowd funding, fiscal responsibility, other forms of informal banking, and remittances, among others to African countries for efficient provision of structures that can aid in the sustenance of development. We conclude that these alternative means of financing development could be a viable policy option to bridge income and development gaps; thereby mainstreaming the process for financial inclusion and sustainability.
Keywords: G20; I00; O10; 330; Finance; Sustainable Development